Analysis of the Relationship Between Leadership and Human Resources Performance Toward the Project Planning Quality of Retail Building - Ken Wastu Narindra; Gusti Ayu Putu Candra Dharmayanti; Kadek Diana Harmayani (International Journal Labs, 2026)
The urgency of this research is based on the strategic role of planning as a fundamental instrument in supporting effective decision making and sustainable achievement of organizational goals. This research aims to examine the influence of leadership and human resource performance on project planning quality in retail building projects. The approaches used were both quantitative and qualitative. Data were obtained through questionnaires distributed to 27 respondents using purposive random sampling. The data were then analyzed using PLS to test causal relationship between the variables. The results of the study indicate that leadership (? = 4.835; p < 0.05) and human resource performance (? = 4.218; p < 0.05) have a positive and significant effect on planning quality. Simultaneously, the two variables are to explain 56% of variance in planning quality (R2 = 0.56%). This finding confirms that increasing leadership effectiveness and human resource performance are the key factor in improving the quality of organizational planning. The research contributes empirically to the understanding of how leadership enhances planning quality through human resource performance in retail construction projects.